Contribution of Academic Satisfaction Judgments to Subjective Well-Being - Zalazar-Jaime, Mauricio F.; Moretti, Luciana S.; Medrano, Leonardo A. (Frontiers in Psychology, 2022)
The role of academic satisfaction (AS) on persistence and successful academic behavior has been the focus of research for decades. Nevertheless, driven by positive educational psychology, subjective well-being has been highlighted as another central feature in the academic path of students. Studies aimed at identifying the variables that contribute to explain different aspects of academic performance have been widely investigated, although studies aimed at identifying the determinants of subjective well-being are still limited. The present paper examined the contribution of AS judgments on subjective well-being (SWB). To this end, it was hypothesized that SWB levels depend on the balance between positive/negative emotions and life satisfaction judgments. Furthermore, it was stipulated that AS has an indirect contribution on SWB, through life satisfaction, whereas the balance of emotions influences both AS judgments and life satisfaction. Using an analysis strategy based on structural equation modeling, the results indicated that the model fitted satisfactorily, explaining 32% of the variance of SWB. Particularly, it was observed that AS judgments contributed to life satisfaction judgments (β = .34). Although no direct contribution of AS on SWB was reported, a total contribution partially mediated by life satisfaction judgments was revealed (total β=.19). These findings support the importance of academic satisfaction judgments, not only because of their importance in academic terms, but also because of their impact on university students' subjective well-being and health.